The Moderating Effect of Personal Experience on False Information Awareness and Reliability of Information to the Psycho-Social Development of Grade 12 Students - Abiño, John Luis D.; Jherwin P. Hermosa (Future Science / FSH-PH Publications, 2025)
In today’s digital age, false information poses a significant threat to adolescents’ cognitive and social development. This study investigates how personal experience influences the relationship between awareness of false information, perceived reliability, and the psycho-social development of Grade 12 students. Employing a mixed-methods approach, the research integrates quantitative surveys and qualitative interviews to evaluate students’ awareness of misinformation, their personal encounters with it, and their perceptions of source credibility. Results show that personal experience with misinformation significantly shapes students’ perceptions of reliability. Those who have encountered false information—either directly or indirectly—tend to exhibit heightened awareness and skepticism. This critical awareness helps them process content more carefully, enabling them to distinguish credible sources from unreliable ones. Quantitative findings reveal that these students are more adept at identifying and questioning misinformation, reducing its negative impact. Qualitative insights further emphasize the psycho-social benefits of such awareness. Students experienced in handling misinformation demonstrate stronger critical thinking skills, increased emotional resilience, and improved social competence, including better communication and interpersonal relationships. The study underscores the value of integrating real-world experiences with misinformation into educational curricula. By embedding critical media literacy and reflective engagement with false information into classroom activities, educators can better prepare students to navigate the complex information landscape. These interventions not only support students’ academic growth but also enhance their emotional and social development, contributing to the cultivation of a more informed, resilient, and socially capable generation.